Where Is She? Finding the Women in Electronic Music Culture - Abtan, Freida (Contemporary Music Review, 2016)
The author discusses the visibility and participation of women in electronic music culture. She argues that most electronic music social networks privilege male inclusion and success, and that skill-sharing is an important strategy to encourage women in the field. To seed this discussion, the author examines her own history with reflections on the gender dynamics within electronic music communities outside the academy, and the role that social and technical currencies play within them. She also discusses Ladies club, a music distribution project that led to several solo female electronic musicians taking the stage and organising events in Montreal during 2007.
Keywords: Culture; Electronic Music; Feminism; Gender; Skills-Sharing

Rap, genre, langage et québéquicité : enjeux et tensions sociolinguistiques de l’accès aux espaces médiatiques à Montréal - Lesacher, Claire (Cahiers internationaux de sociolinguistique, 2016)

DJ Mini and Montreal’s Vulgar Dance Music - Madden, David (Dancecult, 2016)
This article advances claims about Montreal’s electronic dance music scene through mapping the career of one of the key actors who shaped the electroclash scene from the early 2000s onwards—music producer/DJ Mini (née Evelyne Drouin). By way of detailing the career of DJ Mini, this text attempts to add to the queer musical narratives currently emerging from music scene analyses. Counter to the experiences of many women DJs and musicians participating in heterosexual and male-dominated music scenes, Drouin received extensive mentoring and support from various informal queer social networks spread throughout the circuits of the city. Not only did she gain access to a local production network of equipment and skill sharing, Drouin was also given access to spaces where she was able to develop production skills on her own time and at her own pace. DJ Mini’s story offers a telling case for the ways in which the politics of access—institutional, social, technological—remain central to the vitality and inclusivity of local music scenes.